Misi Gereja Dalam Pengembangan Praktek Penginjilan Pribadi Dan Pemuridan Generasi Z - Joni Manumpak Parulian Gultom (Sekolah Tinggi Teologi Arastamar Bengkulu, 2022)
Generation Z has a low spiritual index of 3.50 compared to the national index of 3.79. It emphasizes the church doing faith deepening and mentoring because they feel alien to spirituality and begin leaving the church. The cause of the low index lies in private practice, namely personal and private loyalty. The index of devotional time and Bible meditation is only 3.0, and compassion-based discipleship evangelism for the lost is very low at 2.63. The question is, how is the church's mission in developing personal practice and evangelism - generation Z discipline? What strategies can take? Objectives [1] Describe the church mission developing personal's practice and evangelism - generation Z discipleship. [2] Describe strategies and methods of outreach to the digital generation. The research method is descriptive qualitative. Contribution of this research to [1] pastors of church missions in outreach to generation Z. [2] Christian teachers in school discipleship [3] For College of Theology as a reference in mission and outreach to the younger generation.